Resistance switching mode transformation in SrRuO(3)/Cr-doped SrZrO(3)/Pt frameworks via a thermally activated Ti out-diffusion process - Jo, Yongcheol (Sci Rep, 2014)
This work reports on a mechanism for irreversible resistive switching (RS) transformation from bipolar to unipolar RS behavior in SrRuO(3) (SRO)/Cr-doped SrZrO(3) (SZO:Cr)/Pt capacitor structures prepared on a Ti/SiO(2)/Si substrate. Counter-clockwise bipolar RS memory current-voltage (I–V) characteristics are observed within the RS voltage window of −2.5 to +1.9 V, with good endurance and retention properties. As the bias voltage increases further beyond 4 V under a forward bias, a forming process occurs resulting in irreversible RS mode transformation from bipolar to unipolar mode. This switching mode transformation is a direct consequence of thermally activated Ti out-diffusion from a Ti adhesion layer. Transition metal Ti effectively out-diffuses through the loose Pt electrode layer at high substrate temperatures, leading to the unintended formation of a thin titanium oxide (TiO(x) where x < 2) layer between the Pt electrode and the SZO:Cr layer as well as additional Ti atoms in the SZO:Cr layer. Cross-sectional scanning electron microscopy, transmission electron microscopy and Auger electron spectroscopy depth-profile measurements provided apparent evidence of the Ti out-diffusion phenomenon. We propose that the out-diffusion-induced additional Ti atoms in the SZO:Cr layer contributes to the creation of the metallic filamentary channels.